Greece, Uruguay and the British Informal Empire: From National Narratives to Global History - Gekas, Sakis; Acosta, Camila (Historein, 2021)
This article adopts a comparative global history approach to reflect on the histories of Greece and Uruguay through the prism of British informal imperial rule. It compares and contrasts the role and impact of the British informal empire on Greece and Uruguay’s economic integration into the globalising economy of the late nineteenth century. The aim of this article is twofold: to reflect on each country’s past to gain a better understanding of them, and to integrate the histories of Greece and Uruguay into the history of globalisation. To achieve this, we examine the place of each country in the globalising economy and the reasons why each country “performed” differently; Uruguay experienced some of the highest living standards in the region and the world while Greece was mired in wars and aggressive nationalist policies that lead to significant territorial (and therefore market) expansion at significant cost to state finances – a history that was marked by economic failures such as the default of 1893. Even that crisis, however, produced different outcomes depending on each country’s place in the globalising British informal empire. This article shows two different paths of integration into a globalising economy shaped by the British financial and commercial order – an order often imposed with consent and occasionally through coercion.